PENGGUNAAN MEDIA SOSIAL SEBAGAI ALAT BANTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP MOTIVASI BELAJAR SISWA DI SEKOLAH MENENGAH ATAS NEGERI 8 KOTA JAMBI - Esa Anggi Rodearni BR Saragih; M yahuda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to discuss the forms of social media use as a learning aid in Islamic Religious Education (PAI) to enhance students’ learning motivation in class XII F7 at SMA Negeri 8 Jambi City, as well as to identify the advantages and disadvantages of using social media in PAI learning, and to describe students’ learning motivation through the use of social media in the learning process. This research employs a qualitative approach with a descriptive method. Data collection techniques include observation, structured interviews, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing/verification following the Miles and Huberman model, with data validity checked through source and method triangulation. The results show that social media platforms such as WhatsApp, Instagram, YouTube, and Google Drive are used as tools for discussion, material sharing, and assignment submission. The use of social media has been proven to increase students’ learning motivation by creating a more interactive, flexible, and creative learning process. Students become more confident in expressing opinions, more active in discussions, and more independent in finding learning materials. However, several challenges were also identified, such as distractions from entertainment content and dependence on technology, which can reduce students’ participation in direct religious activities. Overall, the use of social media has a significant positive impact on improving students’ motivation to learn Islamic Religious Education, as long as it is used appropriately and guided by teachers.